2015
DOI: 10.1177/1099800414565815
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Family-Based Intervention Program on Childhood Obesity

Abstract: The purpose of this quasi-experimental study was to assess the efficacy of a family-based (FB) weight-loss and behavior-modification intervention among overweight/obese children (age 9-11 years) and their parents in Taiwan. The intervention group (52 child-parent dyads) participated in an FB program for 7 weeks. The control group (55 child-parent dyads) received an educational pamphlet about obesity prevention. The children's body mass index (BMI) z-scores were the primary outcome variable. The parents' BMI, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Cognitive and behavioral interventions have been employed in Taiwan with obese children and adolescents, but benefits were not observed in a long‐term follow up (Shih, Fan, & Hsiung, ). In a more recent study conducted in Taiwan with overweight or obese sixthgraders and their parents, those who participated in a nurse‐led intervention program for 7 weeks compared to a control group had healthier food available at home, improvement in physical activities, reduced video activity, and significant reductions in BMI of both parents and children (Chen, Kao, Hsiu, Wang, & Hsu, ). Providing parents and their children the opportunity to participate in such a program altered the home environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive and behavioral interventions have been employed in Taiwan with obese children and adolescents, but benefits were not observed in a long‐term follow up (Shih, Fan, & Hsiung, ). In a more recent study conducted in Taiwan with overweight or obese sixthgraders and their parents, those who participated in a nurse‐led intervention program for 7 weeks compared to a control group had healthier food available at home, improvement in physical activities, reduced video activity, and significant reductions in BMI of both parents and children (Chen, Kao, Hsiu, Wang, & Hsu, ). Providing parents and their children the opportunity to participate in such a program altered the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing dynamic physical activity and reducing the use of video devices can help children develop healthy lifestyles (Lin, Lin, Yang & Chou, ). Nurses can conduct family interventions similar to that of Chen et al (), which could support behavioral change and activities and a lower BMI for both parents and children, thus reducing adolescent obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Chen, Kao, Hsu, Wang, and Hsu (2015) tested a family-based weight loss intervention for 9- to 11-year old children with 107 parent-child dyads. The intervention was delivered in four 2-hour biweekly education sessions that focused on nutrition and behavior modification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The minimum sample size of children was calculated according to the criteria for cluster-randomized trial design [32], because community child centers were allocated as clusters into intervention and control groups. We used BMI z-score as a primary outcome variable [33]. Chen, Kao, Hsu, Wang, and Hsu's (2015) study showed a significant improvement in BMI z-scores among children, with means (standard deviations (SD)) of 2.8 (1.16) and 2.4 (1.09) in the intervention and control groups, respectively; the mean difference between two groups was 0.4 after a seven-week family-based intervention [33].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…We used BMI z-score as a primary outcome variable [33]. Chen, Kao, Hsu, Wang, and Hsu's (2015) study showed a significant improvement in BMI z-scores among children, with means (standard deviations (SD)) of 2.8 (1.16) and 2.4 (1.09) in the intervention and control groups, respectively; the mean difference between two groups was 0.4 after a seven-week family-based intervention [33]. Accordingly, we took 0.8 as the mean difference based on the assumption that the present study may show a two times higher effect size than Chen et al's (2015) study because of the multi-level interventions in addition to the family-based intervention and the longer duration.…”
Section: Study Design and Participantsmentioning
confidence: 99%